Fenomena Calon Tunggal dalam Demokrasi Indonesia - Teguh Ilham (Jurnal Ilmiah Administrasi Pemerintahan Daerah, 2020)
Single candidates phenomena have experienced an upward trend in the dynamics of Regional Head Elections (Pilkada) in Indonesia, starting from the 2015 regional elections, and continuing to the 2017, 2018, and in the 2020 regional elections which will be held shortly. This research is a qualitative research with a descriptive approach which aims to describe how the emergence of a single candidate in Indonesian democracy and what are the factors that cause the single candidate to continue to emerge. Based on the discussion, it was found that the single candidate originated from the granting of a judicial review of Law Number 8 of 2015. Then the emergence of single pairs of candidates in various regions was due to the reluctance of other candidates to participate in the pilkada due to the high electability of a single candidate, the rules for legislative members. or other public officials to resign at the time of nominating, political party pragmatism, and the tough requirements to become a candidate.